Drug-Loaded Polymeric Nanoparticles for Cancer Stem Cell Targeting - Li, Binbin; Li, Qinghua; Mo, Jingxin; Dai, Honglian (Frontiers in Pharmacology, 2017)
Cancer stem cells (CSCs) have been reported to play critical roles in tumor initiation, propagation, and regeneration of cancer. Nano-size vehicles are employed to deliver drugs to target the CSCs for cancer therapy. Polymeric nanoparticles have been considered as the most efficient vehicles for drug delivery due to their excellent pharmacokinetic properties. The CSCs specific antibodies or ligands can be conjugated onto the surface or interior of nanoparticles to successfully target and finally eliminate CSCs. In this review, we focus on the approaches of polymeric nanoparticles design for loading drug, and their potential application for CSCs targeting in cancer therapy.